Efektivitas Edukasi Berbasis Keluarga terhadap Pencegahan Baby Blues Syndrome di Puskesmas Umanen Atambua - Ahmad Mumtaz Tauba; Yusfina Modesta Rua; Elfrida Dana (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Baby Blues Syndrome is a common psychological condition experienced by postpartum mothers, characterized by mood swings, anxiety, and emotional instability. Without proper intervention, it may progress into postpartum depression. Family support is a crucial protective factor, and family-based education has been identified as an effective preventive strategy. Objective: This community service aimed to evaluate the effectiveness of family-based education in preventing Baby Blues Syndrome among postpartum mothers at Puskesmas Umanen, Atambua. Method: This activity was conducted in March 2026 using a quasi-experimental pretest–posttest design involving 40 postpartum mothers and their family members. The intervention consisted of structured family-based education, including psychoeducation, emotional support strategies, and coping mechanisms. Baby Blues symptoms were measured using the Edinburgh Postnatal Depression Scale (EPDS). Data were analyzed using the Wilcoxon test. Result: The results showed a significant decrease in Baby Blues symptoms after the intervention, with the mean EPDS score decreasing from 11.2 to 6.5 (p < 0.001). Approximately 85% of mothers demonstrated improved emotional stability, and family members showed increased knowledge and involvement in maternal care. Conclusion: Family-based education is effective in preventing Baby Blues Syndrome and improving maternal emotional well-being. This approach is recommended to be integrated into routine maternal healthcare services at primary healthcare centers.